2023
DOI: 10.1039/d2fo02645g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulberry leaf or mulberry leaf extract on glycemic traits: a systematic review and meta-analysis

Abstract: Mulberry leaf extracts (MLE) have numerous biological properties, such as regulating sugar and lipid metabolism, reducing blood glucose, increasing insulin secretion. The aim of this study was to perform a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
1
4
0
2
Order By: Relevance
“…On the other hand, our results are congruent with other studies that analyzed the hypoglycemic effect of different crops, including sesame 44 , which had a favorable effect on blood glucose levels in a systematic review and meta-analysis of controlled clinical trials. Another study also reported 45 ) this effect, particularly on the glycemic traits of mulberry leaf, they found that these antidiabetic properties were attributed to some phytochemicals that were also reported in our review, such as polysaccharides in Chenopodium quinoa 18 , flavonoids in Smallanthus sonchifolius 9 , 26 , 37 ) and phenols in Solanum tuberosum 14 , 27 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…On the other hand, our results are congruent with other studies that analyzed the hypoglycemic effect of different crops, including sesame 44 , which had a favorable effect on blood glucose levels in a systematic review and meta-analysis of controlled clinical trials. Another study also reported 45 ) this effect, particularly on the glycemic traits of mulberry leaf, they found that these antidiabetic properties were attributed to some phytochemicals that were also reported in our review, such as polysaccharides in Chenopodium quinoa 18 , flavonoids in Smallanthus sonchifolius 9 , 26 , 37 ) and phenols in Solanum tuberosum 14 , 27 .…”
Section: Discussionsupporting
confidence: 82%
“…A pesar de haber encontrado revisiones sistemáticas y en algunos casos metanálisis que evaluaron el efecto hipoglucemiante de distintos cultivos andinos en los últimos años, se identificó que estas revisiones se centraron en otros cultivos que no fueron seleccionados en esta revisión. Entre estos se halló Ipomea batatas (camote) en 2021 (42) , Cuminum cyminum (comino) en 2021 (43) , Sesamum indicum (sésamo) en 2022 (44) , y Morus alba (morera) en 2023 (45) . De igual manera, se encontró una revisión reciente sobre el cultivo Moringa oleifera (moringa) (46) , que también fue utilizado como complemento en uno de los estudios seleccionados (32) , pero que esta revisión fue publicada justo después de que se completa-rá dicho estudio.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In China, mulberry leaf has been clinically used as a traditional Chinese medicine for thirst (equivalent to diabetes in modern medicine) since ancient times [12]. Many scholars at home and abroad have reported on diabetes treatment with mulberry leaves, mostly focusing on the hypoglycemic effect of polysaccharides and flavonoids in mulberry leaves [13][14][15][16]. Iminosugars and sugar derivatives are effective antidiabetic agents [17][18][19].…”
Section: Introductionmentioning
confidence: 99%